2019
DOI: 10.1186/s12886-019-1219-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of Intraductal Meibomian gland probing combined with intense pulsed light in treating patients with refractory obstructive Meibomian gland dysfunction: a randomized controlled trial

Abstract: BackgroundThis study aims to optimize the therapeutic regimen for refractory obstructive meibomian gland dysfunction (o-MGD) patients by combining intraductal meibomian gland probing (MGP) and intense pulsed light (IPL) to enhance their positive effects and reduce their limitations.MethodsThis randomized, assessor blind study includes 45 patients (90 eyes) with refractory o-MGD who were divided into 3 groups via allocation concealment: IPL (group I, received an IPL treatment course: 3 times at 3-week intervals… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 31 publications
0
46
1
Order By: Relevance
“…There are some differences between both devices such as the treatment schedule. The E > Eye system is usually applied in three or four sessions, performed on days 1, 15, 45, and 75 [ 63 , 70 , 71 ], while the M22 system is usually applied in three sessions, separated by 3 or 4 weeks [ 62 , 71 , 72 ]. The spot size is 15 × 40 mm in E > Eye and 15 × 35 mm in the M22, and the cooling system is Airflow in the E > Eye and ChillTip™ Contact in the M22.…”
Section: Light-based Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some differences between both devices such as the treatment schedule. The E > Eye system is usually applied in three or four sessions, performed on days 1, 15, 45, and 75 [ 63 , 70 , 71 ], while the M22 system is usually applied in three sessions, separated by 3 or 4 weeks [ 62 , 71 , 72 ]. The spot size is 15 × 40 mm in E > Eye and 15 × 35 mm in the M22, and the cooling system is Airflow in the E > Eye and ChillTip™ Contact in the M22.…”
Section: Light-based Devicesmentioning
confidence: 99%
“…Piyacomn et al [ 70 ] (I) observed a higher and faster improvement in the MG function in patients who combined conventional eyelid hygiene and IPL than in those patients who performed hygiene alone. Huang et al [ 72 ] (I) compared IPL with intraductal MG probing. They reported that the combination of both methods was more effective than separately in improving symptoms, BUT, meibum grade, and telangiectasias.…”
Section: Light-based Devicesmentioning
confidence: 99%
“…IPL can be used alone or as a helpful supplementary therapy combined with other in-office procedures, especially in recalcitrant MGD cases. Various papers reported positive results obtained by the combined use of IPL with meibomian gland expression [ 26 ], meibomian gland probing [ 29 ], and low-level light therapy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 The approach to using gland probing as first intervention for MGD not responding to conventional therapy of warm compresses, massage and artificial tears was evaluated in a recently published randomised controlled trial. 28 Researchers found best clinical results with statistically significant improvement in standardised patient evaluation of eye dryness scores, tear break up time, meibum grade and lid telangiectasia using probing as initial therapy to physically release fixed obstructions and restore ductal integrity followed by subsequent IPL to 'inhibit telangiectasia' as compared with probing or IPL alone. Gland probing alone was found to provide statistically significant improvement in lid tenderness when compared with intense pulsed light (IPL) alone (p<0.001).…”
Section: Clinical Sciencementioning
confidence: 99%